Understanding the Role of the Antioxidant System and the Tetrapyrrole Cycle in Iron Deficiency Chlorosis - Santos, Carla S.; Ozgur, Rengin; Uzilday, Baris; Turkan, Ismail; Roriz, Mariana; Rangel, António O.S.S.; Carvalho, Susana M.P.; Vasconcelos, Marta W. (Plants (Basel), 2019)
Iron deficiency chlorosis (IDC) is an abiotic stress often experienced by soybean, owing to the low solubility of iron in alkaline soils. Here, soybean lines with contrasting Fe efficiencies were analyzed to test the hypothesis that the Fe efficiency trait is linked to antioxidative stress signaling via proper management of tissue Fe accumulation and transport, which in turn influences the regulation of heme and non heme containing enzymes involved in Fe uptake and ROS scavenging. Inefficient plants displayed higher oxidative stress and lower ferric reductase activity, whereas root and leaf catalase activity were nine-fold and three-fold higher, respectively. Efficient plants do not activate their antioxidant system because there is no formation of ROS under iron deficiency; while inefficient plants are not able to deal with ROS produced under iron deficiency because ascorbate peroxidase and superoxide dismutase are not activated because of the lack of iron as a cofactor, and of heme as a constituent of those enzymes. Superoxide dismutase and peroxidase isoenzymatic regulation may play a determinant role: 10 superoxide dismutase isoenzymes were observed in both cultivars, but iron superoxide dismutase activity was only detected in efficient plants; 15 peroxidase isoenzymes were observed in the roots and trifoliate leaves of efficient and inefficient cultivars and peroxidase activity levels were only increased in roots of efficient plants.